Computer-aided spice program for deep sub-micron devices - Yeo, Boon Hwang. (2008)
This thesis presents an automated circuit analysis tool called SPICESoft, which main objective is to help circuit designers in sensitivity computation and circuit analysis, as well as process and device engineers in their respective fields. These can be achieved through a unique function provided by SPICESoft - the linking process parameters to device parameters, and ultimately to circuit performance. The links between the device parameters and process parameters, as well as the computation needed to implement into SPICESoft are described in detail.